THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT: EXAMINING TEACHER AND STUDENT COLLABORATION IN PUBLIC ELEMENTARY SCHOOLS - Umamah, Fitriah Khoirul; Sholihah, Mar`atus (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
Education is a process of individual development aimed at acquiring knowledge and skills and improving the quality of human resources to achieve better outcomes. SDN Kencong 01 is one of the elementary schools that has implemented the P5 (Project to Strengthen Pancasila Student Profile) program within the Kurikulum Merdeka, achieving a collaboration rate between teachers and students of up to 80%, despite facing challenges such as limited teacher training, inadequate facilities, and variations in students’ abilities and motivation. This research employed a qualitative method with a phenomenological approach to describe the direct experiences of students and teachers in implementing the P5 program with the theme of sustainable living, mainly focusing on the sub-theme of sorting organic, inorganic, and hazardous (B3) waste. Data were collected through observations, interviews, and document analysis involving the principal, 6 teachers, and 163 students from grades 1, 2, and 3 as the research subjects. The findings reveal that collaboration between teachers and students in this project successfully enhanced students’ sense of cooperation (gotong royong), independence, and critical thinking skills. Implementing outing class activities to the landfills (TPA) enabled students to engage in experiential learning, which aligns with Piaget’s constructivist theory. As a follow-up, the school can further develop sustainable programs, such as providing teacher training on the concept of the P5 program. This research offers valuable insights into the effectiveness of P5 in shaping students’ character and can serve as a reference for other elementary schools.